-2=-2(1)+b

Simple and best practice solution for -2=-2(1)+b equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2=-2(1)+b equation:


Simplifying
-2 = -2(1) + b

Multiply -2 * 1
-2 = -2 + b

Add '2' to each side of the equation.
-2 + 2 = -2 + 2 + b

Combine like terms: -2 + 2 = 0
0 = -2 + 2 + b

Combine like terms: -2 + 2 = 0
0 = 0 + b
0 = b

Solving
0 = b

Solving for variable 'b'.

Move all terms containing b to the left, all other terms to the right.

Add '-1b' to each side of the equation.
0 + -1b = b + -1b
Remove the zero:
-1b = b + -1b

Combine like terms: b + -1b = 0
-1b = 0

Divide each side by '-1'.
b = 0

Simplifying
b = 0

See similar equations:

| 4h-22=-7 | | 5x^3+6x-20x-24=0 | | x+78=-284 | | -8(2x+3)= | | -167=-5+9n | | 7=3m+8 | | 8y-4y+11=-33 | | -7y+(13y-25)=15+18y | | 1/2(24-2h)=40 | | 5.5=4(1.5)+b | | 11=1+3n+4 | | -9+s=-1 | | (W+9)(w+8)=12 | | 5=-w-3 | | 3ln(7x)=24 | | x+3x^2-2=250 | | b/2+3=9 | | 1/2(p+4)=6p-9 | | -3(4x-1)=15 | | 5x=y*y | | -8q-6=10 | | 20-5x=2x+6 | | 5.7t+6.96=-32.37 | | 5p-p=16 | | (3+5i)(2-14i)= | | 16y=-(22y-15)-28 | | 2x-3+4x=49 | | 3/7w-11=4/7w | | 12-6(x+4)+10x=2x+2(2x+6) | | -8+(-15x-10)-20x=28 | | 12-6x(x+4)+10x=2x+2(2x+6) | | x=3/10 |

Equations solver categories